Planning Special Events - Reba Ellen Hicks; Ricky Telg; Tracy Irani (EDIS, 2013)
Learning how to plan special events is an important skill that can benefit you and your organization. This publication is designed to help you understand what special events are and how to conduct them. After reading this publication, you will be able to explain how event sites are chosen, what criteria are used to plan events, and how to handle site permits, contracts, and budgets. You also will learn the five critical stages in planning a special event and how to evaluate an event. This 6-page fact sheet was written by Reba Ellen Hicks, Ricky Telg, and Tracy Irani, and published by the UF Department of Agricultural Education and Communication, July 2013.